Melanoma Early Detection: Big Data, Bigger Picture - Petrie, Tracy (J Invest Dermatol, 2018)
Innovative technologies, including novel communication and imaging tools, are impacting dermatology in profound ways. A burning question for the field is whether we will retrospectively react to innovations or proactively leverage them to benefit precision medicine. Early detection of melanoma is a dermatologic area particularly poised to benefit from such innovation. This session of the Montagna Symposium on Biology of Skin focused on provocative, potentially disruptive advances, including: crowdsourcing of patient advocacy efforts, rigorous experimental design of public education campaigns, research with mobile phone applications, advanced skin imaging technologies, and the emergence of Artificial Intelligence (AI) as a diagnostic supplement.